Analysis Of The Application Of 5-Finger Hypnosis Relaxation Therapy In Reducing Pain Levels In Post-Operative Fracture Patients In The Graha Mandiri Room On The 2nd Floor Of The Dr Iskak Tulungagung Regional General Hospital - Aprillia Nuril Hidayanti (Universitas STRADA Indonesia, 2026)
A fracture is a complete or partial disruption of the continuity of bone structure. The term fracture refers to the loss of continuity of bone or cartilage, either totally or partially. In short, a fracture is a broken bone caused by trauma or physical force (Andri et al., 2020). This study aims to determine how the application of the 5-finger hypnosis relaxation technique reduces pain levels in patients who have undergone closed fracture surgery in the Graha Mandiri Room on the 2nd floor of Dr. Iskak Tulungagung Regional General Hospital.This study is a case study with a descriptive narrative design. The sample used in this study consisted of 2 respondents with data collection methods using interviews for primary data collection and medical records for secondary data collection and analyzed descriptively in accordance with nursing documentation. The results of the study found that 2 patients who were respondents experienced a decrease in pain levels measured using the Numeric Rating Scale (NRS). Respondent 1 decreased from a pain level of 8 to 6, and respondent 2 decreased from a pain level of 7 to 4. Pain levels can be influenced by various factors. The interventions provided were only non-pharmacological support given alongside analgesics. Other factors include gender, age, severity of injury, and others.